Changes in a function of transformation as the challenges of tomorrow - Todosijević Snežana; Todosijević Miloš; Katanić Zoran; Radosavljević Damnjan (Mining and Metallurgy Engineering Bor, 2020)
In the world of growing uncertainty, a change is the road without real purpose. Upcoming events can be successfully planned and controlled in a shorter time perspective. With time distance from the current standing point, the level of uncertainty increases while probability of outcomes of events that occurred with an effect of change decrease. Dominant challengers of changes in the enterprises are the technical progress and competition. Reaction of an enterprise is its answer on challenges of changes. At the beginning, we think that we know where the change will take us, and expressed if it will be a fact for us to last as long as possible, because of the fact that at some point end will come to the existing, because a change with some other working change is inevitable. Ability to understand changes is a condition to its implementation. Changes in terms of development require an adaptation and active recurrent action, and who manages to adapt to the developing trends and conditions of environment will last and exist, who does not, will disappear.